Risk of stroke and transient ischemic attack after elective cardioversion of atrial fibrillation: a nationwide study in Finland. (3rd October 2022) - Itainen-Stromberg, S; Lehto, M; Halminen, O; Putaala, J; Haukka, J; Mustonen, P; Linna, M; Kalatsova, K; Aro, A; Hartikainen, J; Airaksinen, K E J
Abstract: Background: Cardioversion is routinely used to restore sinus rhythm in patients with atrial fibrillation (AF). Elective cardioversion (ECV) is associated with an increased risk of thromboembolic complications even during adequate oral anticoagulation (OAC). Purpose: The aim was to analyze the incidence of ischemic stroke and transient ischemic attack (TIA) after first-ever ECV of AF in patients using guideline-recommended OAC. Methods: This nationwide register-based study includes all (N=9625) AF patients undergoing their first-ever ECV between 2012 and 2018 in Finland. Data was obtained from the Finnish health care registers, including both primary and special health care. The risk of stroke and TIA within 30 days after ECV were estimated in patients using OAC. Results: The mean age of patients was 68 (±9.9) years, 61.2% were men, and the mean CHA2DS2-VASc score was 2.6 (±1.6, range 0–9). Warfarin was used in 6245 (64.9%) and non-vitamin K oral anticoagulants in 3380 (35.1%) cardioversions, of which 1453 (15.1%) was rivaroxaban, 1246 (12.9%) apixaban, 635 (6.6%) dabigatran, and 46 (0.5%) edoxaban. Twenty-nine (0.3%; 95% confidence interval [CI] 0.2–0.4%) ischemic strokes or TIAs occurred within 30 days after ECV (median 3 days, interquartile range 2.0–8.5) (Figure 1 and Table 1). In warfarin-treated patients experiencing stroke or TIA, the mean INR value before ECV and at the time of stroke or TIA were 2.5 (±0.5) and 2.5 (±0.5), respectively. One of the patients had INR-value <2.0 before ECV and at the time of stroke and one patient had INR value <2.0 before ECV. Conclusion: In our nationwide study, the rate of stroke and TIA after first-ever ECV was low (0.3%) in all OAC groups. Funding Acknowledgement: Type of funding sources: Public hospital(s). Main funding source(s): Helsinki and Uusimaa Hospital District